P14.04.A TrackingTERTpromoter andIDH1mutations in liquid biopsies - suitable biomarkers for disease monitoring in glioma patients?. (5th September 2022) - Bruckner, K; Madlener, S; Lang, A; Kiesel, B; Furtner-Srajer, J; Hainfellner, J; Haberler, C; Spiegl-Kreinecker, S; Dorfer, C; Slavc, I; Gojo, J; Rössler, K; et al.
Abstract: Background: Mutations within the telomerase reverse transcriptase promoter ( TERTprom ) and isocitrate dehydrogenase ( IDH ) account for the most common genetic alterations in gliomas. Each of these mutations impact clinicopathologic diagnosis and course of diseases. While TERTprom mutations are frequently detected in glioblastoma, IHD mutations are assigned to astrocytoma of grade 2-4, thus mostly associated with better prognosis. In the era of precision oncology, molecular profiling and continuous monitoring of treatment response or relapse are of increasing importance. Accordingly, this study aims to detect TERTprom and IDH mutations in plasma-derived cell-free (cf)DNA of gliomas. The mutant allele frequencies (MAF) will be compared retrospectively to clinico-pathological parameters including extent of resection and tumor progression. Material and Methods: Digital droplet PCR (ddPCR) analyses were performed using the QX200TM Digital Droplet System from BioRad. First, to evaluate probes for ddPCR, genomic DNA of several brain tumor cell models (n=6) and tumor tissue (n=1), as well as cfDNA of plasma (n=3) from samples with known TERTprom and IDH mutation status was investigated. For detection of IDH mutations, the unique assay ID dHSaMDV2010055 (IDH1p.R132H) and for TERTprom mutations the TaqMan dPCR Liquid Biopsy Assays for C228T (Hs000000092) and C250T (Hs000000093) were used. The results of ddPCR were analyzed with QuantaSoftTM software and the MAF was calculated Results: To validate the detection method for IDH1 R132H, we analyzed the MAF in one tissue and corresponding plasma sample of a confirmed IDH1 -mutated astrocytoma. In addition, plasma from one astrocytoma grade 2-3 as well as from an IDH1 -mutated glioblastoma was tested. Interestingly, both astrocytoma cases exhibited undetectable or very low MAF ranging from 0.1 to 1% in tissue as well as in plasma samples, while in plasma from the high-grade glioblastoma case, IDH1 R132H was detected with a frequency of 1.9%. Due to the high GC content of the TERT promoter region, amplification steps are challenging. Accordingly, we first optimized ddPCR conditions for C228T and C250T probes by adding 7-deaza-2-deoxyguanosine-5-triphosphate (7-ddGTP) in varying concentrations to each ddPCR reaction. When using 4µM of 7-ddGTP per sample, a clear separation between mutant and wild-type droplets was reached, detecting MAF between 36-63% in DNA from cell culture models. Conclusion: Within this pilot study we optimized the ddPCR method for the detection of IDH1 R132H and TERTprom mutations in plasma and tissue samples. Subsequently, we hypothesize that these mutations are suitable liquid biomarkers correlating with extent of resection and tumor progression in gliomas.